Bioferroelectricity in Nanostructured Glycine and Thymine: Molecular Modeling and Ferroelectric Properties at the Nanoscale - Bystrov, V. S.
Nanostructured aminoacid glycine and nucleobase thymine are very important for various biomedical applications. Experimentally, these structures demonstrate piezoelectric and polar properties. But the value of polarization and its switching behavior are not clear yet. In this work, computational modeling of glycine polymorphic phases (alpha and beta) and thymine nanostructures was performed using a combined method with LDA first principle calculations of atomic optimized crystal structures in AIMPRO code on Linux cluster combined with molecular semi-empirical PM3 calculations by HyperChem 8.0. The developed molecular model and calculated parameters are compared with recent measurements using piezoresponse force microscopy (PFM) at the nanoscale.